Small Bowel Carcinoid: The "Dancing Bowel Sign" on 18F-FDOPA PET/CT. (December 2016) - Helali, Mehdi; Heimburger, Céline; Rohr, Serge; Goichot, Bernard; Imperiale, Alessio
Abstract : Abstract: The localization of small bowel (SB) neuroendocrine tumors (NETs) remains a diagnostic challenge in clinical practice. In about a third of cases, SB-NETs are multiple at diagnosis. However, the sensitivity of conventional presurgical diagnostic investigations is not exhaustive. 18 F-FDOPA (6-L- 18 F-fluorodihydroxyphenylalanine) PET seems to be a valuable diagnostic technique for the detection of midgut NETs. According to our experience, a delayed PET/CT acquisition centered on abdominopelvic region and performed after oral hydration may improve the detection of primary tumor and the identification of patients with multifocal SB-NETs who could benefit from a more accurate intraoperative palpation of the entire SB.